Elastic neutron scattering at 96 MeV from 12C and 208Pb - Klug J. (2014)
A facility for detection of scattered neutrons in the energy interval 50-130 MeV, scattered nucleon detection assembly, has recently been installed at the 20-180 MeV neutron beam line of The Svedberg Laboratory, Uppsala. First results on elastic neutron scattering from 12C and 208Pb at 96 MeV incident neutron energy are presented. This experiment represents the highest neutron energy where the ground state has been resolved from the first excited state in neutron scattering. The results are compared with modern optical model predictions.